‘The Zyrian Faustus’ Kallistrat Zhakov: the national and the universal - Cозина, Елена (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The paper presents the creative works by Kallistrat Zhakov – a Komi poet, writer, philosopher, and scholar of the Silver Age. The author investigates the ways in which Zhakov integrated images and symbols belonging to the world culture and Russian culture with the native Komi folklore and mythology. The connections of Zhakov’s earliest poems with the symbols of Hindu philosophy and religion are identified. Zhakov’s place in the Russian “pagan renaissance” of the beginning of the 20th century is indicated. The author reconstructs the typology of Zhakov’s characters which, being connected with his philosophical cosmological model of history, is primarily oriented on Russian literature.